Identifying an Alternative Hydride Transfer Pathway for CO2 Reduction on CdTe(111) and CuInS2(112) Surfaces. Issue 1 (23rd December 2021) - Li, Lesheng; Martirez, John Mark P.; Carter, Emily A.
Abstract: To ascertain if CdTe(111) and CuInS2 (112) photoelectrodes exhibit the same carbon dioxide (CO2 ) reduction mechanism as found for GaP, with adsorbed 2‐pyridinide (2‐PyH –* ) as active intermediate, the feasibility of 2‐PyH –* formation on these surfaces must be assessed. Via density functional theory, we conclude that although thermodynamically possible, 2‐PyH −* formation on CdTe(111) or CuInS2 (112) is hindered kinetically. A different CO2 reduction pathway, distinct from GaP's mechanism, must be operative. We predict that surface hydride (H −* ) readily forms on CdTe(111) and CuInS2 (112) and direct surface hydride transfer (HT) to CO2 dominates over transfer to adsorbed pyridine (Py * ). Direct HT to CO2 has a large thermodynamic driving force and zero activation barrier on both surfaces. This reaction becomes slightly more spontaneous with adjacent Py * on both surfaces, rationalizing experiments where Py slightly enhances CO2 reduction on CdTe and CuInS2 . We thus conclude, Py is largely a spectator in CO2 reduction on these electrodes, unlike its key role as hydride shuttle on GaP. HT from H −* to CO2 also competes effectively with hydrogen evolution on these two surfaces, explaining the observed selectivity for CO2 reduction over hydrogen evolution. Finally, formic acid readily adsorbs on CuInS2 (112), which may facilitate the observed methanol formation. Abstract : Solar cell materials, e.g., CdTe and CuInS2, potentially can serve also as photoelectrocatalysts. Of particular interest is whether they can act as photocathodes for CO2 reduction to fuels. Density functional theory reveals mechanistic details of CO2 reduction on their surfaces, predicting dominance of direct surface hydride transfer to activate CO2, foregoing the need for pyridine as a co‐catalyst.